2008
DOI: 10.1104/pp.108.120154
|View full text |Cite
|
Sign up to set email alerts
|

Rh-PIP2;1, a Rose Aquaporin Gene, Is Involved in Ethylene-Regulated Petal Expansion    

Abstract: Aquaporins are water channel proteins that facilitate the passage of water through biological membranes and play a crucial role in plant growth. We show that ethylene treatment significantly reduced petal size, inhibited expansion of petal abaxial subepidermal cells, and decreased petal water content in rose (Rosa hybrida 'Samantha'). Here, we report the isolation of a plasma membrane aquaporin (PIP) gene, Rh-PIP2;1, and characterized its potential role in ethylene-inhibited petal expansion. Rh-PIP2;1 is mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(148 citation statements)
references
References 111 publications
6
140
0
1
Order By: Relevance
“…Some authors reported high expression of PIP2 in other tissues such as leaves (Sakurai et al, 2008), stigmas (Bots et al, 2005), and flower petals (Ma et al, 2008). To our knowledge, this is the first report of in situ hybridization of PIP2 in the stem liber of trees.…”
Section: Discussion Ethrel Induced a Concomitant Increase In Latex Yimentioning
confidence: 82%
“…Some authors reported high expression of PIP2 in other tissues such as leaves (Sakurai et al, 2008), stigmas (Bots et al, 2005), and flower petals (Ma et al, 2008). To our knowledge, this is the first report of in situ hybridization of PIP2 in the stem liber of trees.…”
Section: Discussion Ethrel Induced a Concomitant Increase In Latex Yimentioning
confidence: 82%
“…The silencing of RhNAC2 and RhEXPA4 in petals by VIGS was performed according to the procedures described by Ma et al (2008) with some modifications. For the construction of the RhNAC2 VIGS vector, we used a 351-bp fusion fragment combining 249 bp from the 59 end of the gene with 102 bp from its 39 end.…”
Section: Silencing Of Rhnac2 and Rhexpa4 In Rose Petals By Vigsmentioning
confidence: 99%
“…In tulips, temperature-dependent flower opening and closing is associated with water uptake by petal tissues, which is suggested to involve AQP activity (Azad et al, 2004). Also direct evidence of the participation of a PIP (RhPIP2;1) in petal cell expansion was demonstrated in rose flowers (Ma et al, 2008). It is reasonable to anticipate the presence of genes for PIP that participate in water uptake during petal growth of opening carnation flowers.…”
Section: Introductionmentioning
confidence: 97%
“…Considering that DcPIP2;1 and DcPIP1;1 are expressed more abundantly than DcPIP1;3 as shown in Figure 2, the stable expression of DcPIP2;1 and DcPIP1;1 suggests that the expression level of these PIPs is high enough for flower opening. In rose petals, the role of PIP2 (Rh-PIP2;1) in the regulation of petal cell expansion was demonstrated (Ma et al, 2008). Since the expression of DcPIP2;1 is highest among DcPIP isoforms, it is plausible that DcPIP2;1 participates in petal growth in carnation flowers like Rh-PIP2;1 in rose petals.…”
Section: Expression Profiles Of Dcpip2;1 and Dcpip1;1 In Carnation Flmentioning
confidence: 99%